Analysis of Soil Chemical Property Variations in Oil Palm Plantations of Different Ages in Part of Saliki Village, Muara Badak District - Toyibulah, Yoga; Khairunnisa, Shopia Ananda (Journal of Agriprecision & Social Impact, 2025)
Oil palm development in Indonesia faces various agronomic constraints, especially related to soil chemical properties that are less supportive of productivity. This study aims to identify the status of soil chemical properties on oil palm land in Saliki Village, Muara Badak District, East Kalimantan, to support more appropriate land management. The research was conducted from September to November 2024 using a purposive random sampling method on 13 hectares of land, with six sampling center points and four subsamples per point. Laboratory analysis was conducted on soil pH, C-organic content, total N, available P, potential K, cation exchange capacity (CEC), and base saturation. The results showed that the soil in the 6-year-old oil palm land had a pH of 3.63-3.93 and base saturation of 13.69-13.81%, while at the age of 15 years, the pH decreased to 3.12-3.38 and base saturation was only 4.62-6.95%. Meanwhile, available P and potential K levels tended to increase with increasing plant age. Based on these findings, fertilization is recommended according to the IOPRI standard for mineral soils as follows: for 6 years old, urea 2.75 kg/year, TSP 1.75 kg/year, and KCl 2.75 kg/year, while for 11 and 15 years old, urea 3.25 kg/year, TSP 2 kg/year, and KCl 3 kg/year. This study emphasizes the importance of periodic monitoring of soil chemical properties as a basis for sustainable management of oil palm plantations.